Analysis Of Factors Related To Delay Time of Ischaemic Stroke Patients at dr. R.Koesma Hospital, Tuban Regency - Henry Sudiyanto; Sudigdo Dwi Prasetyo; Arief Fardiansyah; Eka Diah Kartiningrum (Journal of Nursing Management Innovations, 2025)
Background of study: Delay time in arrival of ischemic stroke patients to the hospital is a special concern because the "golden period" for receiving thrombolysis therapy is missed.Aims and scope of paper: The purpose of this study was to analyze the relationship between knowledge, residence status, distance of residence and use of ambulances with delays time in arrival of ischemic stroke patients.Methods: The design of this study was correlational analytic with a cross-sectional design. The total population was 79 ischemic stroke patients in May 2025. The number of samples was 66 patients taken using the simple random sampling technique. Data collection using questionnaires, data analysis using the Spearman test.Result: The results of the study based on the Spearman statistical test with a significance level = 0.05, obtained the results that there was a relationship between the knowledge factor and delays time in arrival (0.001 <0.05), there was a relationship between the residence status factor and delays time  in arrival (0.001 <0.05), there was a relationship between the ambulance use factor and delays time in arrival (0.002 <0.05) and there was no relationship between distance of residence factor and delays time in arrival (0.160>0.05).Conclusion: There are many factors that cause delays time in the arrival of ischemic stroke patients. The researcher hopes that further researchers can continue research on factors that influence the delay time in arrival of ischemic stroke patients so that they can find the right solution to overcome the problem of late arrival of ischemic stroke patients.